2015
DOI: 10.1002/2014jg002646
|View full text |Cite
|
Sign up to set email alerts
|

Dam‐triggered organic carbon sequestration makes the Changjiang (Yangtze) river basin (China) a significant carbon sink

Abstract: Worldwide dam building in large river basins has substantially altered the carbon cycle by trapping much of the riverine transported particulate organic carbon (POC) in terrestrial reservoirs. Here we take the Changjiang (Yangtze) River basin, in which~50,000 dams were built over the past 50 years, as an example to evaluate the effect of dam building on POC sequestration. We report the characteristics (elemental composition, radiocarbon and stable carbon isotopic compositions, and Raman spectra) of bulk POC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 80 publications
(226 reference statements)
6
63
1
Order By: Relevance
“…For the Yangtze River basin, the estimated 2030 reservoir OC burial and mineralization fluxes are 172 and 152 Gmol per year (2.1 and 1.8 Tg C per year). The corresponding total OC removal by reservoirs (172+152=324 Gmol per year) agrees well with the reduction in riverine OC flux since the 1950s of 408±158 Gmol per year, derived independently by Li et al 42. using sediment core data from the lower reaches of the Yangtze River.…”
Section: Resultssupporting
confidence: 86%
“…For the Yangtze River basin, the estimated 2030 reservoir OC burial and mineralization fluxes are 172 and 152 Gmol per year (2.1 and 1.8 Tg C per year). The corresponding total OC removal by reservoirs (172+152=324 Gmol per year) agrees well with the reduction in riverine OC flux since the 1950s of 408±158 Gmol per year, derived independently by Li et al 42. using sediment core data from the lower reaches of the Yangtze River.…”
Section: Resultssupporting
confidence: 86%
“…This result is in accordance with previous findings that the primary production of aquatic ecosystems is more limited by phosphorus than by nitrogen [70]. The impact of dams should also be taken into consideration in explaining DOC spatial variability [71]. Positive correlations between dam density and DOC concentration may be attributed to the elevated algae growth following the construction of dams [72].…”
Section: Environmental Controls On Doc Concentrationssupporting
confidence: 91%
“…Sources of C org buried in marine sediments are commonly inferred from the C/N ratios and isotopic compositions of δ 13 C org and δ 15 N. Previous studies have revealed that terrestrial organic carbon in suspended particle matter from the Yangtze River is characterized by values of C/N 14.6 ± 4.6 (on average) (Wu et al, ), δ 13 C org from −26.6‰ to −24.8‰ (Li et al, ; Yu et al, ), and δ 15 N between 1.18‰ and 4.14‰ (Deng et al, ). Marine‐derived organic matter is typically assumed to have C/N < 10 (Meyers et al, ), δ 13 C org between −22‰ and −18‰ (Ramaswamy et al, ), and δ 15 N with mean values of around 5‰ to 7‰ (Lamb et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the burial of C org in large river‐dominated continental margins are primarily controlled by changes in the terrestrial sediment supply (Syvitski et al, ), SARs (Allison et al, ), hydrodynamics (Tesi et al, ), and biological processes (Ramirez et al, ). There were dramatic alterations in the transfer of suspended particles from the land to the sea between the 1950s and 2015, associated with river damming and cultivated land changes in the drainage basin, and the particle loads and amounts of terrestrial C org to the YRE decreased by >60% and >86%, respectively (Figure S2; Li et al, ; Yang et al, ). Significant changes in sediment load will inevitably decrease SARs and enhance physical erosion and/or bioturbation, thereby influencing the burial and preservation of sedimentary C org in modern sediments (Ramirez et al, ).…”
Section: Discussionmentioning
confidence: 99%